-1/3t-5/6=-89/30+5t

Simple and best practice solution for -1/3t-5/6=-89/30+5t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/3t-5/6=-89/30+5t equation:


t in (-oo:+oo)

(-1/3)*t-(5/6) = 5*t-89/30 // - 5*t-89/30

(-1/3)*t-(5*t)-(5/6)-(-89/30) = 0

(-1/3)*t-5*t-5/6+89/30 = 0

32/15-16/3*t = 0 // - 32/15

-16/3*t = -32/15 // : -16/3

t = -32/15/(-16/3)

t = 2/5

t = 2/5

See similar equations:

| 8-2/3a=3/4a+8 | | -b-5=-17+3b | | -5/6x+4=43/3-6x | | 4/7+5x=3/5x+328/35 | | -3/5d+8=-8/5+d | | 8+6x=-2/3x+184/3 | | 5+2w=w-4 | | 1/4+2x=4/5x+25/4 | | 4+3/4w=6/7w+219/56 | | -x+1/3=-5/12+2x | | 3/10+3/7t=6t-152/35 | | -1/10-1/7t=6/7t-61/10 | | 2b+8=136/15+2/3b | | -5w-7=7w+101 | | 1/7b+4=668/77-5b | | 3w-8=6w-29 | | 4t-1=39-t | | 4+2x=3/4x-7/2 | | 3/4+t=-4t+93/44 | | 4a+8=109/11-3a | | 3w+5=19/3-1/3w | | x-8/9=-x-116/9 | | 5/6w-7=-146/3+5w | | 5m-3=4/7m-1/21 | | -a+10=-3a-12 | | -3/4a+3=111/2-6a | | 7t+3=107-6t | | b+3=-7b+27 | | -5/7+2/7x=2x-125/7 | | 7-5/7m=1/6m+845/126 | | 6-4/5a=1/2a-31/10 | | 1+7d=-2/3d-11/12 |

Equations solver categories